Perioperative endophthalmitis prevention in cataract surgery in Mazovia and Greater Poland in 2013 and 2014 - Grabska-Liberek, Iwona; Majszyk-Ionescu, Julita; Tesla, Piotr; Gaca-Wysocka, Magdalena; Grzybowski, Andrzej (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Aim : This is the first overview of practice patterns in endophthalmitis prevention after cataract surgery in Poland. Material and methods : The study is based on a survey carried out in 33 centres performing cataract surgery in two provinces of Poland (a total of 8.8 million inhabitants, i.e. 23% of the entire country population). Approximately 39.000 cataract surgery procedures are performed in these regions annually, i.e. 20% of all cataract surgery procedures in Poland. The questionnaire-based survey focused on the following aspects: duration of preoperative antibiotic treatment, type of antiseptics, intraoperative administration of antibiotics and duration of postoperative antibiotic treatment. Results : All surveyed centres use povidone-iodine as antiseptic on the periocular skin and conjunctival sac, and perioperative topical antibiotics are adopted by most. Intracameral cefuroxime is increasingly used in endophthalmitis prevention. Conclusion : The methods of endophthalmitis prevention vary widely between ophthalmology departments and clinics in Poland, there is no scientific rationale for most preventive measures used and a further debate is needed among Polish ophthalmic surgeons on optimal practice patterns.